Resolution of Music and Song Copyright Disputes Through Arbitration in Providing Legal Protection for Owners - Simanjuntak, Edison; Harjono, Dhaniswara K.; Pieris, John; Panjaitan, Hulman; Bethlen, Andrew (International Journal of Social Service and Research, 2025)
The Resolution of Music and Song Copyright Disputes Through Arbitration in Providing Legal Protection for Owners in Indonesia is traditionally managed by the Commercial Court, which is often criticized for being slow, costly, and inefficient, thereby failing to offer optimal legal protection for creators. This situation highlights the need for alternative dispute resolution methods. This study analyzes the challenges of resolving copyright disputes through the Commercial Court and examines arbitration as a faster, more effective alternative for protecting music and song creators' rights in Indonesia. Using a normative legal research approach with legislative and conceptual methods, the research involved literature studies of primary and secondary legal materials. Data were analyzed qualitatively through descriptive analysis and deductive reasoning to assess legal synchronization, case studies, and a comparison between litigation and arbitration. Findings show that Commercial Court processes take 160 to 250 days on average, entail high costs, and involve complex bureaucracy, often resulting in inadequate protection for creators. In contrast, arbitration, especially through the Intellectual Property Arbitration and Mediation Agency (BAM HKI), provides a faster resolution (typically 90–180 days) and is conducted by intellectual property specialists, though its rulings require district court enforcement. The study concludes that arbitration is a viable and strategic alternative to litigation for music copyright disputes. It recommends raising awareness and encouraging the use of BAM HKI among creators and policymakers to improve accessible, efficient, and specialized legal protection, thereby strengthening Indonesia’s intellectual property landscape.